From hero to zero: how commercialism ruined community radio in Flanders. (1st December 2008) - Evens, Tom; Hauttekeete, Laurence
In this article, we analyze to what degree a situation of ruinous competition or commercialism affects the economic viability of local radio in Flanders and its duty to supply societal diversity. By examining evidence from both quantitative and qualitative survey approaches, we found that many idealistic, non-commercial stations were pushed out of the market by the rise of large-scale networks and that the overall financial performance of these stations has dramatically deteriorated. Furthermore, the ongoing competition for listeners has driven stations to a market conformity approach leading to similar programming strategies and to shrink local content. With structural handicaps challenging local radio's viability, we aim to formulate some major recommendations for the reorganization of local broadcasting to strengthen both its economical and societal value.